A Developing A Website For Reporting Internship Participants' Activities At The Medan City Communication And Information Service - Heni Wulandari; Suherman Suherman; Muhammad Irfan Dzaky; Zahra Balqis (INFOKUM, 2025)
The rapid advancement of digital technology has driven government institutions to adopt efficient and transparent reporting systems. This study focuses on the development of a website for reporting internship participants' activities at the Medan City Communication and Information Service. The objective is to create a digital platform that facilitates real-time activity reporting, improves data accuracy, and enhances communication between interns and supervisors. The website is developed using a structured system development life cycle (SDLC) approach, incorporating user-friendly features such as activity logs, progress tracking, and automated report generation. The findings indicate that the implementation of this website significantly streamlines the reporting process, reduces administrative workload, and ensures better monitoring of internship activities. This research concludes that a web-based reporting system provides an effective solution for managing internship programs, improving efficiency, and supporting digital transformation in government institutions. The study offers insights for further advancements in digital reporting systems to enhance operational effectiveness in public sector organizations.